Ocean acidification influences the gene expression and physiology of two Caribbean bioeroding sponges - John T. Morris; Ian C. Enochs; Michael S. Studivan; Benjamin D. Young; Anderson Mayfield; Nash Soderberg; Nikki Traylor-Knowles; Graham Kolodziej; Derek Manzello (Frontiers in Marine Science, 2023)
Introduction Coral reef ecosystems are experiencing increased rates of carbonate dissolution due to losses in live coral cover coupled with the impacts of ocean acidification (OA) on coral reef calcifiers and bioeroders. While the stimulating effect of OA on bioerosion has been demonstrated experimentally, predominantly in the Pacific, the underlying physiological and molecular mechanisms behind the response are still poorly understood. Methods To address this, we subjected common zooxanthellate ( Cliona varians ) and azooxanthellate ( Pione lampa ) Caribbean sponges to pre-industrial (8.15 pH), present-day (8.05 pH), and two future OA scenarios (moderate OA, 7.85 pH; extreme OA, 7.75 pH) and evaluated their physiological and transcriptomic responses. Results The influence of OA on sponge bioerosion was nonlinear for both species, with the greatest total bioerosion and chemical dissolution rates found in the 7.85 pH treatment, then not increasing further under the more extreme 7.75 pH conditions. A trend towards reduced bioerosion rates in the 7.75 pH treatment occurred regardless of the presence of algal symbionts and suggests that the sponges may become physiologically impaired under prolonged OA exposure, resulting in diminished bioerosion potential. These findings were supported by the RNA-seq analysis, which revealed differentially expressed genes involved in a stress response to OA, in particular, suppressed metabolism. Discussion This may indicate that the sponges had reallocated energy resources towards more critical physiological needs in response to OA as a survival mechanism under stressful conditions. These data reveal that while the bioerosion rates of excavating sponges in Caribbean reef ecosystems may increase under moderate OA scenarios, this OA-stimulation may plateau or be lost at extreme end-of-century pH conditions, with implications for the dissolution and long-term persistence of reef habitat structures.